2018
DOI: 10.1039/c8ta00525g
|View full text |Cite
|
Sign up to set email alerts
|

High thermoelectric performance of n-type Bi2Te2.7Se0.3via nanostructure engineering

Abstract: BiSbTe has been realized as an ideal p-type thermoelectric material near room temperature; however, its commercial applications are largely restricted by its n-type counterpart that exhibits relatively inferior thermoelectric performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 26 publications
4
91
0
Order By: Relevance
“…As the current density rolls back to 0.1 A g −1 , the specific capacity can be returned to 331.1 mAh g −1 . The above results indicate that the ED‐MoS 2 @CT electrode possesses the superior potassium storage properties, which are not only superior to the contrast samples (for the detail information, see Figure S12 in the Supporting Information) but also comparable for most previously reported PIB anode materials (Figure e) . Notably, the fabricated ED‐MoS 2 @CT electrode exhibits the outstanding cycling stability at high current densities.…”
Section: Resultssupporting
confidence: 65%
“…As the current density rolls back to 0.1 A g −1 , the specific capacity can be returned to 331.1 mAh g −1 . The above results indicate that the ED‐MoS 2 @CT electrode possesses the superior potassium storage properties, which are not only superior to the contrast samples (for the detail information, see Figure S12 in the Supporting Information) but also comparable for most previously reported PIB anode materials (Figure e) . Notably, the fabricated ED‐MoS 2 @CT electrode exhibits the outstanding cycling stability at high current densities.…”
Section: Resultssupporting
confidence: 65%
“…Similar effect is achieved by embedding nano‐SiC particles along the GBs of BiSbTe . Later studies yield improvement of the Seebeck coefficient and PF in nanocomposite materials, such as Bi 0.4 Sb 1.6 Te 3 /SiO 2 , Bi 2 Se 0.3 Te 2.7 /Al 2 O 3 , Bi 0.5 Sb 1.5 Te 3 /ZnO, Bi 0.3 Sb 1.7 Te 3 /SiC, Bi 2 Te 0.7 Se 0.3 /InSb, Bi 0.4 Sb 1.6 Te 3 /Zn 4 Sb 3 , and BiSbTe/Te n 2− polyanions 8b,41,43,44. Interestingly, Pakdel et al decorated the GBs of Bi 0.5 Sb 1.5 Te 3 with Sb 2 O 3 nanoparticles, and concluded that the EF effect contributes to avoiding degradation of the TE properties for durations as long as 24 months.…”
Section: Applications Of the Energy Filtering Effect To Different Clamentioning
confidence: 72%
“…The peak ZT of pristine polycrystalline SnSe (≈0.6 at 773 K) [23] is much lower than that of the single crystalline counterparts. [25] So far, several effective strategies have been adopted to enhance the electrical conductivity of polycrystalline SnSe, such as alkali metal (Li, Na, K), [23,26] Ag, [27,28] Cu, [29] and Zn [30] doping at Sn sites and Sn vacancies. [25] So far, several effective strategies have been adopted to enhance the electrical conductivity of polycrystalline SnSe, such as alkali metal (Li, Na, K), [23,26] Ag, [27,28] Cu, [29] and Zn [30] doping at Sn sites and Sn vacancies.…”
mentioning
confidence: 99%
“…[31] In particular, a high ZT value (≈1.3 at 773 K) has been reported for Ag doped SnSe samples. Few strategies have been successful in reducing the κ L of polycrystalline SnSe, even though secondary phases such as AgSnSe 2 , [27] PbSe, [32] ZnSe, [30] and SnTe [33] have been used. In addition, further reducing the already ultralow lattice thermal conductivity of SnSe is clearly a challenge.…”
mentioning
confidence: 99%